Clinical course of perianal fistulas in Crohn's disease. Issue 5 (November 1995) - Makowiec, F; Jehle, E C; Starlinger, M
Abstract : The clinical course of perianal fistulas and associated abscesses was evaluated prospectively in 90 patients with Crohn's disease. Fistula type, rectal disease, faecal diversion, and immunosuppression were examined as prognostic indicators for fistula healing and recurrence. Median follow up was 22 months. The outcome was evaluated with life table analysis. Prognostic factors were analysed by multiple regression. Inactivation was achieved in all patients. The risks of recurrent fistula activity were 48% at one year and 59% at two years. Fistulas were healed in 51% after two years but reopened in 44% within 18 months of healing. Faecal diversion and absence of rectal disease decreased recurrence rates (p = 0.019/0.04) and increased healing rates (p = 0.005/0.017). The outcome in patients with trans-sphincteric fistulas was better than that in those with ischiorectal fistulas but worse than in patients with subcutaneous fistulas (p = 0.015 for healing; p = 0.007 for recurrent fistula activity). After initial treatment about 20% of the patients were symptomatic and about 10% had painful events per six month period. Incontinence was rare and did not increase during the study period. Perianal fistulas and associated abscesses can be controlled safely by simple drainage of pus collections. Frequent reinfection and re-opening after healing of fistulas are characteristic. Fistula type, rectal disease, and stool contamination influence the clinical course. Only a few patients, however, have continuous symptoms from perianal fistulas.